2019
DOI: 10.1111/ijfs.14459
|View full text |Cite
|
Sign up to set email alerts
|

Production of flavonoid and lignan aglycones from flaxseed and soy extracts by Bifidobacterium strains

Abstract: Flaxseed and soybean are an important source of phytochemical compounds, mainly lignans and isoflavones, but also of flavones, flavanones and flavonols. These compounds appear mainly glycosylated in plant food and are converted into aglycones by the intestinal microbiota, increasing their bioavailability. In this work, we analyse the ability of Bifidobacterium strains (n = 25) to produce lignan and flavonoids aglycones from flaxseed and soybean extracts. Most of the Bifidobacterium strains increased the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…Several studies have linked improvements in gut health with the increase in gastrointestinal AO capacity following intake of AOs such as polyphenols and tocopherols [137]. Polyphenols such as lignans and flavonoids-both products of fermentation of plant components by bifidobacteria-possess an AO effect [138,139]. In the study of Braune and Blaut, the ability of Bifidobacterium strains (n = 25) to produce lignan and flavonoids aglycones from flaxseed and soybean extracts were examined [140].…”
Section: Other Probiotic Metabolites and Cellular Components With Antioxidant Propertiesmentioning
confidence: 99%
“…Several studies have linked improvements in gut health with the increase in gastrointestinal AO capacity following intake of AOs such as polyphenols and tocopherols [137]. Polyphenols such as lignans and flavonoids-both products of fermentation of plant components by bifidobacteria-possess an AO effect [138,139]. In the study of Braune and Blaut, the ability of Bifidobacterium strains (n = 25) to produce lignan and flavonoids aglycones from flaxseed and soybean extracts were examined [140].…”
Section: Other Probiotic Metabolites and Cellular Components With Antioxidant Propertiesmentioning
confidence: 99%
“…However, similar experiments carried out using strains of bifidobacteria with soybean and flaxseed extracts showed very different results to those observed in the present study with respect to antioxidant activity and the concentration of phenolic compounds, with most of the Bifidobacterium strains showing an increase in antioxidant activity and the concentration of phenolic compounds. 4 Bifidobacterium strains did not appear to be involved in the catabolism of phenolic compounds.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, their bioavailability requires their conversion into aglycones via the action of ⊎-glycosidases to produce quercetin, kaempferol, naringenin, herbacetin, quercetagetin, myricetin and eriodictyol in the case of flavones, flavanones and flavonols. 16 Previously, Peirotén et al 4 observed that Bifidobacterium strains transformed the glycosides of a wide range of flavonoids and lignans, increasing the concentrations of SECO, daidzein, genistein, naringenin, eriodyctiol and apigenin. Moreover, Bifidobacterium pseudocatenulatum and Bifidobacterium breve strains produced a large amount of herbacetin in addition to quercetin and quercetagetin, and increased the kaempferol concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations